Luminescence Applied in Sensor Science - Prodi, Luca.; Montalti, Marco; Zaccheroni, Nelsi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Molecular Logic Gates and Luminescent Sensors Based on Photoinduced Electron Transfer, by A. Prasanna de Silva and S. Uchiyama; Luminescent Chemical Sensing, Biosensing, and Screening Using Upconverting Nanoparticles, by D. E. Achatz, R. Ali, and O. S. Wolfbeis; Luminescence Amplification Strategies Integrated with Microparticle and Nanoparticle Platforms, by S. Zhu, T. Fischer, W. Wan, A. B. Descalzo, and K. Rurack; Luminescent Chemosensors Based on Silica Nanoparticles, by S. Bonacchi, D. Genovese, R. Juris, M. Montalti, L. Prodi, E. Rampazzo, M. Sgarzi, and N. Zaccheroni; Fluorescence Based Sensor Arrays, by R. Paolesse, D. Monti, F. Dini, and C. Di Natale; Enantioselective Sensing by Luminescence, by A. Accetta, R. Corradini, and R. Marchelli
Molecular Logic Gates and Luminescent Sensors Based on Photoinduced Electron Transfer, by A. Prasanna de Silva and S. Uchiyama -- Luminescent Chemical Sensing, Biosensing, and Screening Using Upconverting Nanoparticles, by D. E. Achatz, R. Ali, and O. S. Wolfbeis -- Luminescence Amplification Strategies Integrated with Microparticle and Nanoparticle Platforms, by S. Zhu, T. Fischer, W. Wan, A. B. Descalzo, and K. Rurack -- Luminescent Chemosensors Based on Silica Nanoparticles, by S. Bonacchi, D. Genovese, R. Juris, M. Montalti, L. Prodi, E. Rampazzo, M. Sgarzi, and N. Zaccheroni -- Fluorescence Based Sensor Arrays, by R. Paolesse, D. Monti, F. Dini, and C. Di Natale -- Enantioselective Sensing by Luminescence, by A. Accetta, R. Corradini, and R. Marchelli.
Keywords: Chemistry; Analytical biochemistry; Chemistry, Organic; Nanochemistry; Chemistry; Organic Chemistry; Analytical Chemistry; Nanochemistry